2009
DOI: 10.1007/s10560-009-0187-8
|View full text |Cite
|
Sign up to set email alerts
|

No Degree, No Job: Adolescent Mothers’ Perceptions of the Impact that Adolescent Fathers’ Human Capital has on Paternal Financial and Social Capital

Abstract: Becoming an adolescent father truncates young males' opportunities to complete high school and secure employment, which can hinder their capacity to contribute financial and social capital to their children. Based on 69 adolescent mother reports, results suggest that whereas employment status is associated with adolescent fathers' physical and financial presence, high school completion is strongly associated with the nature and quality of parenting and co-parenting behaviors. Implications for school counselors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
17
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 37 publications
2
17
0
Order By: Relevance
“…African American fathers who lack financial resources may view themselves as failures and withdraw from their family (Toth & Xu, 1999). Low-income mothers are more likely to remain in a relationship with their child’s father if he is employed than if he is unemployed (Futris et al, 2010). Thus, we predicted that education and income would predict the presence of the biological father and mother in the home.…”
Section: Enduring Vulnerability Factorsmentioning
confidence: 99%
“…African American fathers who lack financial resources may view themselves as failures and withdraw from their family (Toth & Xu, 1999). Low-income mothers are more likely to remain in a relationship with their child’s father if he is employed than if he is unemployed (Futris et al, 2010). Thus, we predicted that education and income would predict the presence of the biological father and mother in the home.…”
Section: Enduring Vulnerability Factorsmentioning
confidence: 99%
“…Labeling this population as "at-risk" characterizes them as a homogenous group and ignores the variability of their behaviors and experiences that impact their educational outcome, which may then consequently influence their fathering behaviors (Futris et al, 2010). Clearly, further research that examines the heterogeneity among these young fathers is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Further, adolescent fathers who dropout and work may be in a better position to support their children in the short term, but those who delay work to complete high school and go on to college may be in a better position to provide later (Pirog-Good, 1996). In fact, adolescent fathers who complete high school maintain more frequent and positive interactions with their child and their child's mother (Futris, Nielsen, & Olmstead, 2010). More education means better jobs, higher income, and a greater likelihood of economic self-sufficiency (Rangarajan & Gleason, 1998).…”
mentioning
confidence: 99%
“…Despite the challenges faced by adolescent fathers in regards to coparenting relationships, studies have suggested that coparenting support may be more important for adolescent fathers wanting to stay involved with children than for adult fathers (Florsheim, Sumida, et al, 2003; Futris, Nielsen, & Olmstead, 2010). One reason is the likelihood that adolescent partner relationships tend to be unstable over time (Gee & Rhodes, 2003).…”
Section: Theoretical Foundationmentioning
confidence: 99%